Формуваня та розвиток джерел міського права Луцька у складі Волинсько-Галицької держави та Великого князівства Литовського - Колодяжна, В.; Kolodiazhna, V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті проаналізовано особливості формування та розвитку джерел права і самоврядних інститутів Луцька в складі різних держав, з’ясовано тяглість розвитку норм українського звичаєвого права етнічних українських земель, набутого за часів Київської Русі, Галицько-Волиньської держави та процес «інкорпорації», «вживлення» іноземних (німецьких, польських) елементів правового досвіду стосовно формування та функціонування державно-правових та самоврядних інститутів на Волині в кінці XIІІ–XVIІ ст.The article analyzes the issue of the formation and development of law sources and self-government institutions in Lutsk, within the periods of different states rule. The study elucidates the continuity in the development of the Ukrainian law norms on the ethnic Ukrainian lands formed during the times of Kievan Rus, Volyn-Halych state and in the process of incorporation of the foreign (German, Polish) elements of legal experience concerning the formation and functioning of the state-legal and self-governing institutes in Volyn at the end of XII century. The main sources of the municipal law formation in the 13th-18th centuries were the following normative acts: «Ruska Pravda», credentials and privileges for granting the city Magdeburg law in 1432, 1497, 1503, 1560, 1576; charter certificates of 1501, 1509, 1547; Certificate of Merit (Brevet) of1457; Sudebnik (Code of Law) of 1468; Charter of the Grand Duchy of Lithuania of 1529 and its revisions of 1566 and 1588; collections of Magdeburg law; and derived from the first - acts of self-government bodies, workshops and court practices.
Formation and Development of the Dources of Lutsk Municipal Law within the Volyn-Halych State and the Grand Duchy of Lithuania
Keywords: джерела права; міське право; магдебурзьке право; Волинсько-Галицьке князівство; Велике князівство Литовське; law sources; municipal law; Magdeburg law; Volyn-Galician principality; Grand Duchy of Lithuania